Wideband Polarization Insensitive Tunable Graphene-Supported Terahertz Metamaterial Absorber - Muhammad Abdul Jabbar; Muhammad Ashar Naveed; Muhammad Zubair; Muhammad Qasim Mehmood; Yehia Massoud (IEEE Photonics Journal, 2023)
Broadband Terahertz (THz) metamaterial absorbers with tunable absorption characteristics have been attracting a lot of attention due to their high demand and utilization in advanced optical systems. Therefore, we propose a single-layer graphene-supported metamaterial absorber with a combination of square, circular and cross-shaped meta-resonators, exhibiting an outstanding absorption of more than 90% from 2.3 THz to 6.4 THz. The overall size of the unit cell is 15 × 15 μm2, which holds graphene-based meta-resonators etched over a lossy dielectric substrate, backed by a 0.2 μm thick gold as a perfect reflector. This design architecture achieves the ultra-broadband absorption features by continuous design evaluation and optimization. The graphene-based metamaterial absorber (GMMA) reveals a polarization-insensitive response, and it also provides above 70% absorption for obliquely incident angles over the large operating bandwidth (2.3–6.4 THz). The polarization conversion ratio (PCR) also approached zero over the wideband of 4.1 THz and its maximum value of 16% was recorded at 4 THz. Furthermore, the amplitude spectra of the proposed GMMA is modulated from 19% to above 90% by stimulating the chemical potential of graphene from 0 eV to 0.7 eV. The simplified design configuration, broadband absorption features, and tunable capability of the GMMA provide the pathway to develop high-speed optical switches, THz detectors, and other opto-electronic devices.